2017
DOI: 10.1002/jsfa.8168
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of fat from ruminants' meat on cardiovascular health and possible strategies to alter its lipid composition

Abstract: In the last few decades there has been increased consumer interest in the fatty acid (FA) composition of ruminant meat due to its content of saturated FAs, which have been implicated in diseases associated with modern life. However, recent studies have questioned the recommendations to reduce intake of fat, saturated FAs and cholesterol as a means of reducing the risk of cardiovascular disease. Interestingly, ruminant meat has some bioactive lipids such as C18:1t11 and C18:2 c9, t11 which have been reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…In contrast with the other saturated fatty acids, stearic acid — a saturated fatty acid with 18 carbon atoms — is considered to not have a negative effect towards humans 25 . Research indicated that stearic acid had no effects on serum total cholesterol concentrations and increased intake of stearic acid reduces the risk of cardiovascular disease similar to intake of oleic acid (C18:1) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the other saturated fatty acids, stearic acid — a saturated fatty acid with 18 carbon atoms — is considered to not have a negative effect towards humans 25 . Research indicated that stearic acid had no effects on serum total cholesterol concentrations and increased intake of stearic acid reduces the risk of cardiovascular disease similar to intake of oleic acid (C18:1) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Humans can obtain n-3 LC-PUFA or their C 18 PUFA precursors from various sources including aquatic (fish, crustaceans, and mollusks), farm livestock products (meat, egg, and milk), oilseeds, fruits, herbs, cyanobacteria and microorganisms (bacteria, fungi, microalgae, and diatoms) 6 . Ruminant meat research has drawn considerable attention because ruminant meat contains some bioactive lipids (including n-3 LC-PUFA) and the fatty acid profiles of ruminant meat can be enhanced through dietary supplementation 7,8 . In this regard, the manipulation of fatty acid profiles in sheep meat via dietary n-3 LC-PUFA supplementation has yielded some promising results.…”
Section: Introductionmentioning
confidence: 99%
“…concentrates rich in linoleic acid or feeding pasture-based diets (Vargas-Bello-Pérez and Larraín, 2017). These strategies are based on increasing ruminal synthesis of vaccenic acid, thereby increasing uptake of the respective fatty acid in duodenum resulting in greater endogenous synthesis of rumenic acid in the mammary gland (Vasta et al, 2009b).…”
mentioning
confidence: 99%